Hubungan Pengetahuan Swamedikasi Influenza terhadap Karakteristik Tenaga Teknis Kefarmasian - Oviana Kristiono; Amelia Rumi; Ririen Hardani (Jurnal Health Sains, 2021)
Self-medication is someone's attempt to treat himself or herself. The role of pharmaceutical technical personnel in self-medicated activities is important, they can provide clear drug information to buyers. So, can prevent the mistake of using drugs to buyers when they are going to self-medication. The research objective was to determine the level of knowledge of pharmaceutical technical personnel about influenza treatment by self-medication and the relationship between demographic characteristics of pharmaceutical technical personnel and level of knowledge This research was conducted by purposive sampling with sample size 125 pharmaceutical technical personnel. The questionnaire was made at Google Form and distributed through the WhatsApp group of pharmaceutical technical personnel. The data collected was analyzed descriptively and used Chi-Square test to see relationship between the level of knowledge and the characteristics of pharmaceutical technical personnel. The results of this study found that a good level of knowledge in pharmacy technical personnel aged 17-30 years (90.52%), final education level of S1 (88.4%), female (91%) and has a service life of <5 years (91%). Based on the results of Chi-Square test can be concluded there is no relationship between the level of knowledge and age, final education level, gender, and years of service.